Three tasks for a dragon - Colfer, Eoin (Candlewick Press, 2023)
"After his father's death, Prince Lir is tricked into embarking on a perilous quest to rescue a maiden from a dragon. The studious young prince is no warrior, but he uses his brains to make himself indispensable to the ill-tempered dragon. However, neither prince not dragon has bargained on the dark magic that manipulates them both -- and it may be left to the maiden herself to save them all. A clever prince, an unsuspectingly powerful woman, and an ornery dragon with heart are at the center of this luminously illustrated classic in the making."--